Arabic Language and Muslim Religious Identity in the Digital Age: Evidence from Mindanao, Philippines - Muhamad Muhajir; Mohamad Syukri bin Abdul Rahman; Khairatul Akmar Bin Ab Latif; Ana Taqwa Wati; Magfur Afnan Fauzi (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
Arabic occupies a central position in Islamic education and religious practice; however, its contribution to Muslim religious value identity in minority contexts facing rapid digital transformation remains underexplored. This study investigates the role of Arabic in shaping Muslim religious value identity in Mindanao, Philippines, while examining the challenges and opportunities arising from technological change. A qualitative case study design was employed using purposive sampling. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving Arabic language teachers, religious leaders, and Muslim youth. The data were analyzed thematically with source triangulation and member checking to enhance trustworthiness. The findings reveal that Arabic functions not only as a medium for accessing Islamic texts but also as a mechanism for internalizing religious values, strengthening communal belonging, and reinforcing Muslim identity. Although digitalization and multilingual environments have reduced reliance on Arabic in everyday religious learning, technology simultaneously provides new opportunities for expanding Arabic education through digital platforms and interactive learning resources. The study demonstrates that sustaining Muslim religious identity requires integrating Arabic language instruction with value-oriented pedagogy and technology-enhanced learning. It contributes a holistic perspective linking language, religion, and digital transformation within a Muslim minority context.